Manufacturing Firms in Developing Countries: How Well Do They Do, and Why? - Tybout, James R (Journal of Economic Literature, 2000)
The manufacturing sectors of developing countries have traditionally been relatively protected. They have also been subject to heavy regulation, much of which has favored large firms. Accordingly, it is often argued that in these countries: (1) markets tolerate inefficient firms, so cross-firm productivity dispersion is high; (2) small groups of entrenched oligopolists exploit monopoly power in product markets; and (3) many small firms are unable or unwilling to grow, so important scale economies go unexploited. Drawing on plant and firm level studies, I assess each of these conjectures and find none to be systematically supported. However, many open issues remain.